The historic Kentucky kitchen : traditional recipes for today's cook - Scaggs, Deirdre A. (The University Press of Kentucky, 2013)
Kitchens serve as more than a place to prepare food; they are cornerstones of the home and family. Just as memories are passed down through stories shared around the stove, recipes preserve traditions and customs for future generations. The rich, diverse heritage of Kentucky's culinary traditions offers a unique way to better understand and appreciate the history of the commonwealth. The Historic Kentucky Kitchen assembles more than one hundred dishes from nineteenth and twentieth-century Kentucky cooks. Deirdre A. Scaggs and Andrew W. McGraw collected recipes from handwritte.